1948
DOI: 10.1021/ja01187a050
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Yields of the Photochemical Reduction of Ceric Ions by Water and Evidence for the Dimerization of Ceric Ions

Abstract: Water solutions containing ceric perchlorate and perchloric acid evolve oxygen when they absorb ultraviolet light and the ceric is reduced to cerous perchlorate.2Baur2a and Weiss and Porret2b studied the photochemical reaction in the full light of a quartz mercury arc lamp. Weiss and Porret obtained maximum gross quantum yields of the order of one-tenth in solutions one-tenth molar in ceric perchlorate and one molar in perchloric acid. Their quantum yields decreased as the cerous perchlorate accumulated.We hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

1951
1951
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(27 citation statements)
references
References 0 publications
0
26
1
Order By: Relevance
“…Several studies [20,21] have found that Ce IV species present in perchloric acid as solvent are Ce 4ϩ , Ce(OH) 3ϩ Concerning the reducer species, t-BuOH, it is well known that for tertiary alcohols the oxidation begins on the carbon atom linked to the hydroxyl group. On the other hand, the stoichiometric equation shows that both acetone and formaldehyde are produced.…”
Section: Formal Mechanismmentioning
confidence: 99%
“…Several studies [20,21] have found that Ce IV species present in perchloric acid as solvent are Ce 4ϩ , Ce(OH) 3ϩ Concerning the reducer species, t-BuOH, it is well known that for tertiary alcohols the oxidation begins on the carbon atom linked to the hydroxyl group. On the other hand, the stoichiometric equation shows that both acetone and formaldehyde are produced.…”
Section: Formal Mechanismmentioning
confidence: 99%
“…Efforts to use solar energy for the purpose of generating chemical energy through the photodecomposition of water can be traced back 30yr (Heidt and Smith, 1948; R i a and Weiss, 1952; Calvin, 1961). Schematically, the reaction can be represented as hv H20 [photosensitizer]' H2 + The energy which is required to transfer one electron from oxygen to hydrogen is 34.16 kcal per equivalent (Handbook, 1965).…”
Section: Introductionmentioning
confidence: 99%
“…Recently Heidt and Smith (2) postulated the existence of a stable dimei-of cerium in ceric perchlorate solution. This assumption enabled them to explain some unusual effects observed in the photochen~ical reduction of ceric ion in perchloric acid.…”
Section: Introductionmentioning
confidence: 99%